Experimental study of Permeable Concrete Pavement with Polypropylene Fibres - Prasanth, M Surya; Snehitha, S M N B; Rao, K Jaya (International Journal of Psychosocial Rehabilitation, 2020)
As the traffic is rapidly increasing, accidents are occurring because of contraction width of roads. The major accidents are observing mainly due to skidding effect especially on rainy seasons. Hence the skidding effect parameter plays an important role on concrete pavements. Also it is the responsibility of the pavement designer to drain the water immediately from the roads. For this reason providing different types of cambers but it is not reaching the requirements and also making discomfort able to the drivers. So the present paper focusing in this problem and came with a concept called permeable concrete with polypropylene fibres to permit the water below the pavement without effecting the pavement surface and underground layers. This type of pavement also absorbs the noise coming from the vehicles and hence it is also beneficial to the environment. The suitable mix design also developed with different proportions of polypropylene fibres to make a permeable concrete pavement. This paper studies the strength parameters of permeable concrete pavement with polypropylene fibres by conducting various tests in the laboratory. The results obtained and the conclusions made were given in this paper.